Parasitism by Campoletis flavicincta on Spodoptera frugiperda in corn - Neto, Fausto da Costa Matos; Cruz, Ivan; Zanuncio, José Cola; Silva, Carlos Henrique Osório; Picanço, Marcelo Coutinho (Pesquisa Agropecuaria Brasileira, 2004)
Parasitism by Campoletis flavicincta (Ashmead) (Hymenoptera: Ichneumonidae) on Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) and consequent reduction of production losses were evaluated on caged corn plants in the field. Treatments consisted of plots infested with 0 (control), 15 and 30 pairs of C. flavicincta with egg masses per cage and plot infested without cage and liberation of the parasitoid. Parasitoid release was done when S. frugiperda larvae were three-day-old. Fifty corn plants (40%) per plot were collected seven days after infestation and S. frugiperda larvae present were reared in glass cups on an artificial diet. Number of S. frugiperda larvae was reduced by C. flavicincta but mortality of the pest and parasitoid sex ratio in laboratory were similar among treatments. Total progeny and female production from collected larvae were similar among densities of released parasitoid. Parasitism rate was higher on 30 than on 15 pairs of C. flavicincta. Damage on corn plants at seven and 14 days after S. frugiperda infestation had similar grades at 0, 15 or 30 C. flavicincta pairs and higher values than the plots without cage. Damage by S. frugiperda was lower at 30 C. flavicincta pairs after 21 days of infestation. Final stand, stand reduction by plant death and corn productivity were similar among treatments.